PERBANDINGAN ANATOMI KAYU RENGAS TEMBAGA (GLUTA RENGHAS L.) DENGAN RENGAS BURUNG (MELANORRHOEA WALLICHII HOOK. f) - Sri Rulliaty (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Wood of renga1tembaga (Gluta renghas L.) and ren,as IJurung(Melanorrhoea wallicbii Hook.(.) ltaue many common limilaritia in the anatonJicalfeatures.Some of the differencel are in the grou feature of wood. Anatomical 1tudy 1hows that the frequency of Pora and raya dimenaion (width and height) of Melanorrhoea wallichii Hook.f. are significantly different compared with those of Gluta renghas L.